2004
DOI: 10.1002/elps.200305883
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organic components of smokeless gunpowders: High‐performance liquid chromatogaphyvs.micellar electrokinetic capillary chromatography

Abstract: The aim of the present study was to verify the analytical performances of high-performance liquid chromatography (HPLC) and micellar electrokinetic capillary chromatography (MEKC) for the separation and qualitative determination of a selected group of organic components of smokeless gunpowders. The HPLC method was based on a gradient reversed-phase elution with a mobile phase composed of 0.17 M H(3)PO(4)/methanol; detection was performed by UV absorption at the wavelengths of 220, 254, and 270 nm. The MEKC exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…This is conceivable both being based on hydrophobic interactions between the stationary or pseudostationary phase and the analytes. The use of diode array UV detection for recording peak spectra proved to be more feasible with CE in comparison to gradient HPLC, because of the lack of gradient-related drift of the detector signal occurring in the latter technique [65].…”
Section: Explosive Analysis and Gunshot Residuesmentioning
confidence: 99%
“…This is conceivable both being based on hydrophobic interactions between the stationary or pseudostationary phase and the analytes. The use of diode array UV detection for recording peak spectra proved to be more feasible with CE in comparison to gradient HPLC, because of the lack of gradient-related drift of the detector signal occurring in the latter technique [65].…”
Section: Explosive Analysis and Gunshot Residuesmentioning
confidence: 99%
“…Smokeless powders are traditionally analyzed in a laboratory setting and require timeconsuming protocols and expensive confirmatory instrumentation. Previous studies cite the use of gas chromatography-mass spectrometry (GC-MS), high performance liquid chromatography (HPLC), ion chromatography, and micellar electrokinetic capillary electrophoresis [5][6][7][8][9][10]. Though the confirmatory result is advantageous, the potential drawbacks for many laboratories are a drain on the economic and time resources.…”
Section: Introductionmentioning
confidence: 99%
“…Stirring, however, was considered to be ineffective by Zeichner and Eldar, who reported that sonication is imperative to achieving an efficient extraction [38]. This is generally followed by centrifugation, which allows for the collection of the supernatant and filtration [8,14,46]. Alternatively, the sample may be concentrated prior to centrifugation by blowing it to near dryness [38], or complete dryness [10][11][12].…”
Section: Solvent Extractionmentioning
confidence: 99%
“…The majority of these studies have been reported since 2010 [2,[7][8][9][10][11][12]. A few studies, including one review [3], prior to 2010 have been included for the purpose of comparison [13][14][15]. This has resulted in a list containing 136 organic compounds that could be associated with smokeless powders and gunshot residue.…”
Section: Organic Gsr Compoundsmentioning
confidence: 99%
See 1 more Smart Citation